Comparison of Reduction in Physical Discomfort Score for Pregnant Women who Attended Prenatal Yoga for 30, 45 And 60 Minutes - Zelita Viana; Dyah Retnoningrum; Siti Patimah (Indonesian Journal of Global Health Research, 2024)
Prenatal yoga is a recommended choice for pregnant women because it can reduce physical discomfort. These activities include breathing exercises, stretches, strengthening positions, and relaxation techniques that help reduce back and neck muscle tension. This research aims to compare the reduction in physical discomfort scores of pregnant women who take part in prenatal yoga for 30, 45 and 60 minutes at Alanda Care, Pangkalpinang City in 2024. This research method is quantitative with pre-experimental design with one group pretest-posttest design. Data collection used the NRS (Numerical Rating Scale) questionnaire which was adopted from Petter and Perri 2005 in Fauziah 2012. The population of this study were all 90 pregnant women who took part in prenatal yoga at Alanda Care, Pangkalpinang City. The sample in this research was 30 respondents. This data was analyzed using the Paired Sample T-Test and Anova test. The results of this research are that the value of the paired T-test results obtained is p value (0.000), this figure is smaller than the α (alpha) value ₌ 0.05. The Anova test results produce a p value = 0.000 which is smaller than alpha 0.05. So it was concluded that there was a difference in the average comparison of the reduction in physical discomfort scores for pregnant women who participated in prenatal yoga for 30, 45 and 60 minutes.